Obligate mutualism within a host drives the extreme specialization of a fig wasp genome - Xiao J-H; Yue Z; Jia L-Y; Yang X-H; Niu L-H; Wang Z; Zhang P; Sun B-F; He S-M; Li Z; Xiong T-L; Xin W; et al. (BioMed Central Ltd)
Background: Fig pollinating wasps form obligate symbioses with their fig hosts. This mutualism arose approximately 75 million years ago. Unlike many other intimate symbioses, which involve vertical transmission of symbionts to host offspring, female fig wasps fly great distances to transfer horizontally between hosts. In contrast, male wasps are wingless and cannot disperse. Symbionts that keep intimate contact with their hosts often show genome reduction, but it is not clear if the wide dispersal of female fig wasps will counteract this general tendency. We sequenced the genome of the fig wasp Ceratosolen solmsi to address this question. Results: The genome size of the fig wasp C. solmsi is typical of insects, but has undergone dramatic reductions of gene families involved in environmental sensing and detoxification. The streamlined chemosensory ability reflects the overwhelming importance of females finding trees of their only host species, Ficus hispida, during their fleeting adult lives. Despite long-distance dispersal, little need exists for detoxification or environmental protection because fig wasps spend nearly all of their lives inside a largely benign host. Analyses of transcriptomes in females and males at four key life stages reveal that the extreme anatomical sexual dimorphism of fig wasps may result from a strong bias in sex-differential gene expression. Conclusions: Our comparison of the C. solmsi genome with other insects provides new insights into the evolution of obligate mutualism. The draft genome of the fig wasp, and transcriptomic comparisons between both sexes at four different life stages, provide insights into the molecular basis for the extreme anatomical sexual dimorphism of this species. © 2013 Xiao et al.; licensee BioMed Central Ltd.
Keywords: Animals; Evolution, Molecular; Female; Ficus; Gene Expression Regulation, Developmental; Genome Size; Genome, Insect; Male; Phylogeny; Sequence Analysis, DNA; Sex Characteristics; Symbiosis; Wasps; 05 Environmental Sciences; 06 Biological Sciences; 08 Information and Computing Sciences